Theoria - Petzäll, Åke (C.W.K. Gleerup, 1935)
"A Swedish journal of philosophy."
Keywords: Philosophy : Periodicals; Psychology : Periodicals; Philosophie : Périodiques; Philosophy; Psychology; Filosofie